Fabrication of Dump Truck Tilting System with Advanced Pneumatics - Raman, Kumar; Thamotharan, C.; Naveen chandran, P.; Sahooand, Debabrata (International Journal of Psychosocial Rehabilitation, 2018)
With the advancement of the transport technologies, companies are trying to find ways to find simpler and cost effective technologies. Our project suggests a simple but advantageous mechanism for the dump truck. A dump truck is used for transporting construction material. They have a tilt-able trolley. The mechanism for this operation is to be enhanced in our project. It proposes the idea of using a folding mechanism coupled with pneumatics to tilt the trolley of the dump truck. The system employs the use of a linkage hinged to together and a pneumatic cylinder is attached to the hinge. Thus when the pneumatic cylinder works in the forward direction, the linkages ate stretched and when it is made to return, the linkages get folded up.